2021
DOI: 10.1093/neuonc/noab228
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma genetic drivers dictate the function of tumor-associated macrophages/microglia and responses to CSF1R inhibition

Abstract: Background Tumor-associated macrophages/microglia (TAMs) are prominent microenvironment components in human glioblastoma (GBM) that are potential targets for anti-tumor therapy. However, TAM depletion by CSF1R inhibition showed mixed results in clinical trials. We hypothesized that GBM subtype-specific tumor microenvironment convey distinct sensitivities to TAM targeting. Methods We generated syngeneic PDGFB-driven and RAS-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…On this note, it may be more important to reprogram microglia than to deplete them for treating glioblastoma. Indeed, a phase II clinical trial of PLX3397 did not show significant efficacy in glioblastoma patients (Butowski et al, 2016), and similarly our data as well as that of (Rao et al, 2022) showed depletion of microglia actually promoted tumor growth. Why these results conflict with prior RCAS-hPDGF-B murine model (Pyonteck et al, 2013; Quail et al, 2016) is not entirely clear, but perhaps it has to do with GSC heterogeneity (Pyonteck et al, 2013; Yan et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On this note, it may be more important to reprogram microglia than to deplete them for treating glioblastoma. Indeed, a phase II clinical trial of PLX3397 did not show significant efficacy in glioblastoma patients (Butowski et al, 2016), and similarly our data as well as that of (Rao et al, 2022) showed depletion of microglia actually promoted tumor growth. Why these results conflict with prior RCAS-hPDGF-B murine model (Pyonteck et al, 2013; Quail et al, 2016) is not entirely clear, but perhaps it has to do with GSC heterogeneity (Pyonteck et al, 2013; Yan et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…Why these results conflict with prior RCAS-hPDGF-B murine model (Pyonteck et al, 2013; Quail et al, 2016) is not entirely clear, but perhaps it has to do with GSC heterogeneity (Pyonteck et al, 2013; Yan et al, 2017). For example, the 005 model consists of OPC- and MES-like cells (Hara et al, 2021) and tumors progressed with CSF1R inhibitor (CSF1Ri) whereas the opposite was seen in the proneural-like PDGF-B-driven tumors (Herting et al, 2017; Quail et al, 2016; Rao et al, 2022). Further research is required to evaluate the response of CSF1Ri in various different glioma subtypes, which will better guide the application of CSF1Ri in human glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also observed differential migratory behaviors depending on the genetic background of the tumor. Previous studies by our lab and others have shown that genetically distinct GBMs respond differentially to CSF-1R inhibition ( Akkari et al., 2020 ; Quail et al., 2016 ; Rao et al., 2022 ), and recent reports have indicated that the genetic makeup of gliomas impacts the cellular composition of the TME ( Akkari et al., 2020 ; Magod et al., 2021 ). Of particular interest is the observation that blockade of CSF-1R signaling reduced the number of TAMs in the syngeneic GL261 GBM model ( Coniglio et al., 2012 ), whereas TAMs are protected from CSF1R inhibitor-induced apoptosis in Ink4a/Arf -deficient GBMs by secreted factors and are instead “re-educated” ( Pyonteck et al., 2013 ).…”
Section: Discussionmentioning
confidence: 90%
“…Results obtained with the CT2A model, of low mutational burden, are more representative of the clinical situation [79]. Furthermore, the hypothesis of CSF1R targeting to impact on TAMMs was generated in a murine model of glioma due to PDGFB amplification, a picture only present in 4–5% of human gliomas: again, a clinical trial based on this failed to produce meaningful gains in patient survival [35 ▪▪ ]. Thus, not only better models are required but more emphasis on patient data is necessary, to avoid the hiatus between laboratory and clinical research, also defined as the ‘valley of death’ [80].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, gliomas may acquire resistance to CSF1R inhibition via the production of insulin-like growth factor-1 (IGF1) by TAMMs and the subsequent activation of the IGF1R-PI3K pathway in tumour cells [37]. Even more importantly, recent evidence suggests that the therapeutic benefit of CSF1R inhibition is strongly context-dependent: while in proneural glioma models, the treatment leads to relevant tumour response and improved survival, in MES-like models, CSF1R inhibitors are inefficient or even detrimental [35 ▪▪ ], likely underpinning their limitations in the heterogeneous and highly dynamic tumour as GBM.…”
Section: Isocitrate Dehydrogenase Wildtype Gliomasmentioning
confidence: 99%